O1-S01.02 The incidence of genital Chlamydia trachomatis in a cohort of young Australian women. (10th July 2011) - Walker, J; Fairley, C; Bradshaw, C; Tabrizi, S; Chen, M; Twin, J; Taylor, N; Donovan, B; Kaldor, J; Hocking, J
Abstract : Background: Chlamydia is a sexually transmitted infection that can cause serious upper genital tract infections, however, in Australia there are limited population data for chlamydia. Understanding the incidence of chlamydia will be important in the design of a chlamydia screening program in Australia. Method: Women aged 16–25 years were recruited from sexual health clinics (SHC) and general practice clinics (GP) in South-Eastern Australia and consented to participate in longitudinal study over a 12-month period. Participants were requested to send back questionnaires and self-collected vaginal swabs through the post which were tested for chlamydia. Results: Overall, 1116 women were recruited from 29 clinics; with a 79% retention rate. C trachomatis prevalence at baseline was 4.9% (95% CI: 2.9% to 7.0%) and incidence rate for the 12-month study period was 4.4 per 100 women-years (95% CI: 3.3% to 5.9%). Prevalent C trachomatis was associated with having had C trachomatis previously [AOR: 2.0 (95% CI: 1.1% to 3.9%)], increased numbers of sexual partners [AOR: 6.4 (95% CI: 3.6% to 11.3%)] and unprotected sex [AOR: 3.1 (95% CI: 1.0% to 9.5%)]. Antibiotic use and older age were protective against having a prevalent infection ([AOR: 0.4 (95% CI: 0.2% to 1.0%)] and [AOR: 0.9 (95% CI: 0.8% to 1.0%)] respectively) and an incident infection ([AHR: 0.1 (95% CI: 0.0% to 0.6%)] and [AHR: 0.4 (95% CI: 0.2% to 0.8%)] respectively). Incident C trachomatis was also associated with more partners [AHR: 4.0 (95% CI: 1.9% to 8.6%)]. More than 20% of women with C trachomatis had a re-infection during the study [20.3% (95% CI: 11.6% to 31.7%)] with an infection rate of 20.0 (95% CI: 11.9% to 33.8%) per 100 women years. The median chlamydia organism load was 1.4×105/5цl and the most common serovar identified was serovar E (51.9%). Conclusion: Chlamydia is a common STI in young Australian women, and an incidence of 4.9 per 100 women years for chlamydia suggests annual testing is appropriate for a chlamydia screening program. The high re-infection rate indicates the importance of partner notification and re-testing 3 months after treatment.